2021
DOI: 10.2196/preprints.31104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Body Mass Index (BMI) Trends Among a Pediatric Dental Patient Population: A Pilot Study. (Preprint)

Abstract: BACKGROUND Over the past few decades, a growing trend of overweight and obesity has emerged among the pediatric population. This is a cause of significant concern as these are significantly correlated to other negative oral and systemic health outcomes over time. Although measurement of body mass index (BMI) is common among pediatric physicians and primary care providers, few studies have explored the feasibility of BMI measurement and analysis from pediatric dental providers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…These results may provide some of the first observations of these shifts among this specific patient population. In fact, recent studies from this group have found that body mass index (BMI) has been steadily increasing among the pediatric and adolescent patient population, with most recent average BMI ranging between 25.6 (overweight) and 31.3 (obese) [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results may provide some of the first observations of these shifts among this specific patient population. In fact, recent studies from this group have found that body mass index (BMI) has been steadily increasing among the pediatric and adolescent patient population, with most recent average BMI ranging between 25.6 (overweight) and 31.3 (obese) [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%